2017
DOI: 10.1007/s00586-017-5283-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of congenital C1 arch anomalies

Abstract: Although some types of congenital C1 arch anomalies are rare, type A defects are relatively common radiological findings that are unreported approximately 45% of the time. Based on the significant association between the anterior and posterior arch defects, we propose possible mechanisms for the formation of the bipartite atlas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
3
20
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to report the prevalence of congenital arch anomalies of C1 through the CT examinations of the cervical spine in Omani population. In the existing literature, the reported prevalence of C1 arch anomalies varied between 0.95% and 5.65% [1,[9][10][11][12][13]. In a study by Geipel [9], congenital C1 defects were found in 4% of 1,613 adult specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to report the prevalence of congenital arch anomalies of C1 through the CT examinations of the cervical spine in Omani population. In the existing literature, the reported prevalence of C1 arch anomalies varied between 0.95% and 5.65% [1,[9][10][11][12][13]. In a study by Geipel [9], congenital C1 defects were found in 4% of 1,613 adult specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, type A posterior arch anomaly was found to be the most common, followed by type B posterior arch anomaly, other types of posterior arch anomalies were not detected. The reported prevalence of various types of posterior arch anomalies were described in Table 2 [1,[9][10][11][12][13]. In all these studies, type A was the most common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a retrospective study of a large number of patients who underwent CT scan of the cervical spine for various reasons, approximately 1.5 to 5% of the patients had posterior arch of atlas defects, whereas approximately 0.46% had a combination of both anterior and posterior defects and the prevalence of an isolated anterior arch of atlas defect was 0.03% [8]. We extrapolate the true incidence of isolated anterior arch of atlas defects in the population to be rarer than this.…”
Section: Discussionmentioning
confidence: 99%